PENGEMBANGAN BAHAN AJAR BERBASIS MULTIMEDIA INTERAKTIF PADA MATERI ANIMASI STOP MOTION MULTIMEDIA UNTUK SMK KELAS XI - Muhammad Arief Santoso; Marianus Subandowo; Retno Danu Rusmawati (Jurnal Education and Development, 2020)
The development of this teaching material research for students can learn independently, actively and creatively in exploring learning resources. This research develops interactive learning multimedia products on stop motion animation material class XI skill competencies of multimedia at SMK Negeri 1 Pungging Mojokerto. The model of developing instructional materials used is the ADDIE Model that is (1) analysis, make a needs analysis; (2) design, made layout of media, instrument preparation, and materials preparation; (3) development, developing interactive multimedia product and formative validation; (4) implementation, apply the product to students and student’s assessment of the product; (5) evaluation, evaluate product that have been given advice by validators by fixing the product according to suggestions. From the analysis of the data, it can be concluded that The Development of learning materials Based of Interactive Multimedia on Stop motion Animation Material is feasible to use with an assessment of the feasibility of the media based on aspects of cognition content is 80%, information presentation is 80%, ease of navigation is 80%, artistic and aesthetic is 80%, and overall function is 80%. And for the total average percentage of the 5 aspects is 80%. For all aspects of the material is 80% and for all aspects of quality by respondents consisting of 34 students of class XI is an average percentage is 83.29%.